Microemboli-monitoring during the acute phase of ischemic stroke: Is it worth the time? - Idicula, Titto T (BioMed Central, 2010)
BACKGROUND: The prevalence of microembolic signals (MES) during the acute phase of ischemic stroke and its influence on outcome is not well studied. The aim of our study was to determine the prevalence of MES, the different factors that are associated with the presence of MES and the association between MES and outcomes in stroke patients investigated within 6 hours after the onset of ischemic stroke. METHODS: We included unselected ischemic stroke patients who underwent microemboli-monitoring within six hours after stroke onset. Microemboli-monitoring of both middle cerebral arteries (MCA) was done for a period of 1 hour using 2-MHz probes applied over the trans-temporal window. Prevalence of MES, predictors for the presence of MES and the association between MES and various outcome factors were analyzed. RESULTS: Forty patients were included. The mean age of the patients was 70 years. The prevalence of either ipsilateral or contralateral MES were 25% (n = 10). The predictors for the presence of MES were older age (OR 9; p = 0.03), higher NIHSS (OR 28; p = 0.02), intracranial stenosis (OR 10; p = 0.04) and embolic stroke (large-artery atherosclerosis and cardioembolism on TOAST classification) (OR 7; p = 0.06). MES were not independently associated with short-term functional outcome, long-term mortality or future vascular events. CONCLUSIONS: MES are moderately frequent following acute ischemic stroke. Microemboli-monitoring helps to better classify the stroke etiology. However, the presence MES did not have any prognostic significance in this study.